KNOWLEDGE ATTITUDE AND PRACTICES AMONG FEMALE HEALTH WORKERS REGARDING REPRODUCTIVE AND CHILD HEALTH SERVICES IN RURAL MEERUT - Jain, Seema; Singh, J V; Bhatnagar, M; Garg, S K; Chopra, H C; Bajpai, S K; Pant, Bhawana (Indian Journal of Community Health, 2007)
.